Tipping sacred cows : kick the bad work habits that masquerade as virtues - Breeden, Jake, 1972- (Jossey-Bass, 2013)
Strategies for overcoming the "sacred cows" that hold people back at workWe all know the "sacred cows" at work'the conventional wisdom to try your best, work well with others, and produce excellent work. But these cherished nuggets of advice, in practice, have a dark side that can lead to career-limiting unintended consequences. Based on Jake Breeden's experience coaching thousands of leaders in 27 countries, and the latest scientific research in behavioral economics, neuroscience, and psychology, Tipping Sacred Cows reveals how to overcome the dangerous behaviors that masquerade as virtues at work, and how to lead with fewer self-imposed limitations and greater results. Identifies the seven most common sacred cows at work, including balance that turns bland, creativity that conceals narcissism, and passion that becomes obsessionOffers simple steps for recognizing and overcoming the potentially career-limiting effects of each of the most common sacred cowsWritten by Jake Breeden, a faculty member at Duke University's Corporate Education program, rated by Businessweek and The Financial Times as #1 in the worldTipping Sacred Cows shines a light on the hidden traps that lie between good intentions and great results, clearing a path so leaders can finally realize their full potential at work. Take this quick 21-question survey to find out which of the seven sacred cows are standing in your way at work.